Implementation of Eco Friendly in the Housekeeping Department of the Conrad Bali Hotel - Wiratama, I Gede; Pitanatri, Made Uttari; Launingtya, Niken (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Eco-friendly is a simple environmentally friendly activity that aims to reduce the impact of waste, especially hotel industry waste. Eco-friendly is a growing trend in the hotel industry, but its implementation still faces several obstacles, including limited understanding regarding the importance of waste management, lack of consistency in implementing Eco-friendly programs and obstacles in changing organizational culture. The aim of this research is to determine the implementation of Eco-friendliness in the housekeeping department at the Conrad Bali hotel. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation studies related to supporting documents such as the Tri Hita Karana certificate and certificates of collaboration with other organizations. Based on the results of research in the field, the Conrad Bali hotel is considered a sustainable hotel, this can be seen from the policies and full support by the management, collaboration with local organizations and communities, the use of more environmentally friendly chemicals, recycling activities, energy and water efficiency. , as well as implementing programs related to Eco-friendliness and consistently following the Tri Hita Karana certification.